Mental health service user experiences of targeted violence and hostility and help-seeking in the UK: a scoping review. (11th December 2017) - Carr, Sarah; Holley, Jessica; Hafford-Letchfield, Trish; Faulkner, Alison; Gould, Dorothy; Khisa, Christine; Megele, Claudia
Abstract : Background: The aim of this research scoping review was to assemble an evidence base for the UK on mental health service user experiences and perspectives on mental health-related targeted violence and hostility ('disability hate crime'). It also aims to address some of the gaps in the knowledge on risk management, help-seeking and prevention from the perspectives of those who experienced targeted violence and hostility because of their mental health problems or psychiatric status. Methods: Seven key mental health and social care bibliographic databases were searched for relevant UK research studies from 1990 until 2016. Grey literature was identified through online searches. A scoping review charting approach and thematic analysis methodology were used to analyse the studies. Results: In total 13 studies were finally included, over half of which used survey methods. All studies included people with experiences of mental health problems. The studies provide information on: the types of potential hate crime; indicate where incidents take place; give some insight into the victims' relationship with the perpetrators; the location of incidents as well as the psychological, social, financial and physical impacts on the victim; the types of help-seeking behaviours adopted by the victims; a range coping strategies that people with mental health problems adopted in response to experiences of targeted violence or abuse. Conclusion: This scoping review provides a UK-based overview of mental health service user concepts and experiences of mental health-related targeted violence and hostility ('disability hate crime'). It reveals some specific issues relating to mental health and disability hate crime. Further investigation into disability hate crime with a specific focus on mental health is required. This is a UK-based overview, which offers a useful comparator for researchers, practitioners and policy-makers internationally.